Britain’s next research choice - Ben Johnson; Will Stone (Science, 2026)
Ten years ago, the Brexit referendum began the United Kingdom’s departure from the European Union (EU), forcing British science to confront a serious question: What place should the UK occupy in European research? No longer qualified to be a full-fledged member of Horizon Europe, the matter of whether to rejoin as an associate member became a totemic issue for the UK. There were serious questions around whether rejoining would be worth the money, especially if it had to pay in more funding than it could win back in grants. UK researchers, however, insisted that association was the best way to protect their access to the most prestigious and attractive funding opportunities. So, when the UK eventually associated in 2024, it was to sighs of relief. But times have changed.